2018
DOI: 10.35791/agrsosek.14.1.2018.19295
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Sektor Unggulan Terhadap Perekonomian Di Kabupaten Jayawijaya

Abstract: This study aims to determine what sectors are the leading sectors and the role of superior sector to the economy within the last 5 years in Jayawijaya regency. This research is conducted for three months starting from June 2017 until August 2017 in Jayawijaya Regency. The data used in this study is secondary data obtained from the Central Bureau of Statistics (BPS) Jayawijaya district. The data is in though using descriptive analysis research method. The research shows that the sectors that are the leading sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
1
5
1
1
Order By: Relevance
“…Jayawijaya Regency is an economic centra for the central mountainous region in Papua Province. The central mountainous region includes the regencies of Nduga, Tolikara, Yalimo, Puncak Papua, Pegunungan Bintang, Mamberamo Tengah, Yahukimo, and Lanny Jaya (Wenda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jayawijaya Regency is an economic centra for the central mountainous region in Papua Province. The central mountainous region includes the regencies of Nduga, Tolikara, Yalimo, Puncak Papua, Pegunungan Bintang, Mamberamo Tengah, Yahukimo, and Lanny Jaya (Wenda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Wenda et al (2018) conducted a search for leading sectors and their role in the economy of Jayawijaya Regency for five years from 2011 to 2015. The results showed that the agricultural; manufacturing; construction; electricity, gas and clean water; trade, hotels and restaurants; financial services; transportation and communication; and services are leading sectors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Untuk meningkatkan kesejahteraan dan pembangunan ekonomi pada suatu daerah harus dilakukan dengan pertumbuhan ekonomi yang berkelanjutan (Pratiwi & Warnaningtyas, 2015). Menurut (Wenda & Tarore, 2018) pertumbuhan ekonomi adalah tolak ukur adanya pembangunan ekonomi pada suatu wilayah. Menurut (Hadi, 2018) dengan pertumbuhan ekonomi wilayah yang tinggi maka akan diikuti dengan kesejahteraan masyarakatnya yang juga akan ikut meningkat.…”
unclassified